Tata Laksana Lambert Eaton Myasthenic Syndrome - Marcellinus Michael Leonard Mardiono; Widyawati Suhendro (Cermin Dunia Kedokteran, 2023)
Lambert-Eaton myasthenic syndrome (LEMS) is a neuromuscular junction disorder resulting from a paraneoplastic or autoimmune reaction. More than half LEMS cases are associated with small cell lung carcinoma (SCLC). The main clinical manifestation is muscle weakness. The pathophysiology is due to the generation of the autoantibodies against voltage-gated calcium channels (VGCCs) on presynaptic nerve terminals leading to a decrease in neurotransmitter acethylcholine (ACh). Various treatments such as tumor treatments, immunomodulatory, and symptomatic treatment have been studied, but further research is needed.